Imidazolinium based porous hypercrosslinked ionic polymers for efficient CO2 capture and fixation with epoxides. Issue 11 (17th May 2017) - Li, Jing; Jia, Degong; Guo, Zengjing; Liu, Yangqing; Lyu, Yinong; Zhou, Yu; Wang, Jun
Abstract : 2-Phenylimidazoline based porous hypercrosslinked ionic polymers afforded high yields in the cycloaddition of epoxides with ambient or diluted CO2 (0.15 bar CO2 and 0.85 bar N2 ) under low or room temperature. Abstract : The efficient capture and chemical conversion of carbon dioxide (CO2 ) requires a solid simultaneously with a large surface area and highly effective active sites. Herein, imidazolinium based porous hypercrosslinked ionic polymers (HIPs) with a high surface area, rich micro/mesoporosity and abundant ionic sites were constructed via the hypercrosslinkage of 2-phenylimidazoline and benzyl halides, in which quaternization and Friedel–Crafts alkylation happened simultaneously to afford ionic polymeric networks. The obtained HIPs were efficient in the selective capture of CO2 and cycloaddition of CO2 with epoxides. High yield, stable reusability and good substrate compatibility were achieved under mild conditions (down to ambient conditions), dramatically outperforming the homogeneous ionic liquid monomer and post-modified analogues. The synergistic adsorption and conversion enabled the efficient low-temperature conversion of diluted CO2 (0.15 bar CO2 and 0.85 bar nitrogen, the simulation of flue gas) catalyzed by HIPs in the presence of co-catalyst ZnBr2 . The in situ formed ionic sites with a high leaving ability being homogeneously embedded in the hypercrosslinked polymeric skeleton responded to the high adsorption and catalysis performance. This work highlights the functional HIPs as a versatile platform to reach efficient CO2 capture and conversion under mild conditions.